Agreement Asymmetries with Adjectives in Heritage Greek - Artemis Alexiadou; Vasiliki Rizou; Foteini Karkaletsou (Languages, 2023)
Research on different populations of heritage speakers (HSs) has demonstrated that these speakers (i) frequently produce fewer adjectives, and (ii) produce more errors in nominal concord than in subject–verb agreement. The first point, (i), has been attributed in the literature to the optionality of adjectives and to the fact that adjectives characterize the literary language and HSs lack familiarity with this register. The second point, (ii), is viewed by other researchers as supporting theories that treat nominal concord as being different from subject–verb agreement. In this paper, we contribute data on production of adjectives and agreement asymmetries with adjectives from heritage Greek. We show that these cannot be viewed as supporting claims with respect to (i) but conclude that nominal concord and subject–verb agreement involve different mechanisms. We furthermore explore ways to account for a slight contrast we observe between prenominal and postnominal agreement.